Women and Climate Change: A Slow Violence Study by Batang Masumai River - Lisa Aulia; Wike Wike; Retty Ratnawati (Wacana: Jurnal Sosial dan Humaniora)
This research aims to explore the experience of women by Batang Masumai river to slow violence. Limited access to water services and infrastructure in rural area affect women who bear the responsibility to meet household water need because they depend on the river as water source and sanitation facilities. Climate change as a form of slow violence that occurred gradual and attritional becomes a major threat to household water security. The method of this qualitative research is interpretative phenomenological analysis. The data is collected through an in-depth interview with four women from low-income households by Batang Masumai river and observation. The result of this reseacrh shows that floods and droughts that become more severe contribute to water availability, accessabiliy, and quality so that women by Batang Masumai river have to walk longer distances to meet clean household water, carry heavy burden load while also exposed to water conflicts in water points. As slow violence becomes more destructive in a long period of time, there is a need for government to fully implement Law 17/2019 regarding Water Resources to help women with limted sources to adapt and build their resiliency.